Fall Prevention: Home Safety Inventory - Leigh Ann Martin; Linda B. Bobroff (EDIS)
Revised! FCS-2229, a 2-page fact sheet by Linda B. Bobroff and Leigh Ann Martin, provides a checklist of changes people can make to reduce risk of falling and keep their home a safe place to live in. Published by the UF Department of Family Youth and Community Sciences, April 2009. 2009 revision unavailable, original 2005 version and 2016 revision included instead.